LEGALITAS DAN OTORITAS FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA DALAM OPERASIONAL LEMBAGA KEUANGAN SYARIAH - Muhamad Ibnu Afrelian; Imahda Khoiri Furqon (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2019)
Islamic financial institutions in their operations require legislation. In addition, practitioners of sharia economics also need a fatwa from the National Sharia Council-Indonesian Ulema Council (DSN-MUI) to guarantee the implementation of Sharia principles in sharia financial institutions. Although the fatwa is basically an advice that can be carried out or ignored, but the DSN-MUI Fatwa if it is related to positive law, the position is the same as the doctrine that is as an amplifier in the legal ruling of a qadhi in a case. The DSN-MUI fatwa also has authority and an important role in making legislation binding, and is used as a positive law in enhancing the development of sharia economics in Indonesia. The legal aspects contained in the DSN-MUI fatwa, can be seen from the absorption of the DSN-MUI fatwa in various regulations relating to the operations of Islamic financial institutions, and have been transformed into the form of laws. Thus, the legal strength of the DSN-MUI fatwa becomes binding in the operations of Islamic financial institutions